Broadcast 41 Women and the Anti-Communist Blacklist - Stabile, Carol A. (Goldsmiths Press, 2020)
Seeking a solution, pioneering women not only imagined, made and wore radical new forms of cycle wear, they also patented their inventive designs. The most remarkable of these were convertible costumes that enabled wearers to secretly switch ordinary clothing into cycle wear.